Zarządzanie jakością w banku z wykorzystaniem systemu ADONIS - Łosiewicz, Ewa (The Quality Management in a Bank with ADONIS System, 2005)
This paper presents banking processes modelling in the quality management. A tool used for modelling is ADONIS - business process management system with the modelling and simulation module. ADONIS system is an useful tool for systematising and ordering of process documentation and other improvement processes in the bank.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 114-122